GENEALOGY AND SILSILA OF SUFI SHEIKHS OF THE KHALWATIYYA ORDER IN THE LEZGIN VILLAGE OF KHLYUT - Zakariaev, Zamir Sahbanovic (History, Archeology and Ethnography of the Caucasus, 2023)
The paper reveals the results of studying the genealogy and the chain of spiritual succession of Sufi sheikhs who lived in the 18th–19th centuries in the mountainous Lezgi village of Khlyut, South Dagestan. A Sufi monastery, known as “Tekke”, was located there. The founder of the monastery was Sheikh Muhammad-‘Ali, who is believed to be of Yemen origin. We present the text and annotated translation of an early list of a valuable historical source in Arabic for the first time. The list has been found to be compiled approximately in the middle of the 18th century, which makes it the earliest surviving document of this kind in Dagestan. It includes both the spiritual genealogy (silsila) and the lineage (nasab) of the Khlyut sheikhs. The author managed to almost completely restore the content of the main text of the document, which became possible due to the presence of two handwritten lists. We conclude that the main text of the late list, with the exception of a small interpolated insert, was carried over from the early list. Both lists end with small late additions with information about two branches of the sheikhs’ descendants. An analysis of the genealogy of Khlyut spiritual figures shows that they were descendants of Sufi sheikhs who lived in northern Shirvan. Silsila contains the names of the most famous medieval Sufis of the Muslim world and goes back to the Yemeni Tabi‘in Uwais al-Qarani, and through him to ‘Ali b. Abi Talib. The mention in the silsila of famous Shirvan sheikhs of the 15th century of the Khalwatiyya order, as well as their successors, who lived in the mountains of southern Dagestan, leaves no doubt that the Khlyut sheikhs also belonged to this Sufi brotherhood. It has been established that the vigorous activity of Khalwatiyya in South Dagestan was not limited only to the Late Middle Ages, but continued later. The Arabic-language inscriptions of the Tekke complex, on the territory of which the burial places of Sufis, the remains of residential buildings and premises for Sufi practices are located, have also been studied.
Keywords: Dagestan; Sufism; the village of Khlyut; sheikh; silsila; Halwatiyya; Tekke